2021
DOI: 10.3390/life11070715
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Gut–Brain Axis in Ischemic Stroke: A Narrative Review with a Focus about the Relationship with Inflammatory Bowel Disease

Abstract: The gut microbiota is emerging as an important player in neurodevelopment and aging as well as in brain diseases including stroke, Alzheimer’s disease, and Parkinson’s disease. The complex interplay between gut microbiota and the brain, and vice versa, has recently become not only the focus of neuroscience, but also the starting point for research regarding many diseases such as inflammatory bowel diseases (IBD). The bi-directional interaction between gut microbiota and the brain is not completely understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Another well-studied clinical example is acute ischaemic stroke, which leads to intestinal ischaemia and dysbiosis, which in turn exacerbate cerebral infarction by enhancing systemic inflammation [ 130 , 131 ]. In addition, dysbiosis is associated with poor outcomes following acute ischaemic stroke as it interacts with the brain through all of the above mechanisms [ 56 , 132 , 133 ].…”
Section: Interaction Of the Gut Microbiota With Key Organs: The Conce...mentioning
confidence: 99%
“…Another well-studied clinical example is acute ischaemic stroke, which leads to intestinal ischaemia and dysbiosis, which in turn exacerbate cerebral infarction by enhancing systemic inflammation [ 130 , 131 ]. In addition, dysbiosis is associated with poor outcomes following acute ischaemic stroke as it interacts with the brain through all of the above mechanisms [ 56 , 132 , 133 ].…”
Section: Interaction Of the Gut Microbiota With Key Organs: The Conce...mentioning
confidence: 99%
“…The main consequences of this immunodepression is infection, to which changes in gut microbiota might contribute by increasing plasma trimethylamine N-oxide levels ( 94 , 95 ). Gut dysbiosis is also a determinant of post-stroke outcomes ( 96 ).…”
Section: The Brain-immune Crosstalk In Ischemic Strokementioning
confidence: 99%
“…Regarding the gastrointestinal system, the sympathetic nervous system may be deleterious, by disrupting production of intestinal mucin, gut permeability ( via noradrenergic-mediated expression of TREM1), and composition of intestinal microbiota ( 78 , 99 ), while the vagal nerve is, on the other hand, more protective. For instance, reducing parasympathetic nerve activity after an acute brain injury stimulates intestinal bacterial proliferation and increases bacterial translocation ( 96 ). It has been recently demonstrated that there are circulating molecular regulators, such as small RNA, that finely control the cholinergic reflex in stroke patients.…”
Section: The Brain-immune Crosstalk In Ischemic Strokementioning
confidence: 99%
“…A review of eighteen studies concluded that aging, inflammation, and different microbial compositions may unequivocally contribute to the development of ischemic stroke ( Lee et al, 2021 ). Older mice with a high Firmicutes / Bacteroidetes ratio were documented to have a higher risk of ischemic stroke and were unable to recover from neurological deficits, contributing to higher mortality ( Spychala et al, 2018 ; Sinagra et al, 2021 ). Aging increases the risk of neurodegenerative, cerebrovascular and cardiovascular diseases and cancer.…”
Section: Agingmentioning
confidence: 99%